2020
DOI: 10.1055/s-0040-1721768
|View full text |Cite
|
Sign up to set email alerts
|

Paradigms in Complex Facial Scar Management

Abstract: The process of scar formation is a sequela of the healing following soft tissue injury extending to, or through, the reticular dermis. Scars, within the head and neck in particular, may be physically disfiguring with resultant psychosocial implications. Mitigation of excessive scar formation during the healing process following surgery, or in the setting of trauma, begins with meticulous soft tissue handling and reconstructive technique. The reconstructive surgeon's armamentarium must therefore include techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 71 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…21 One possible explanation for these results, is that due to delayed onset of muscle inactivity, BTXA injections must be performed 1 to 2 weeks prior to anticipated incision or laceration to have effect at the time of acute healing. 22 In addition to BTXA-induced wound immobility, in vitro studies and animal studies have also shown that BTXA may promote wound healing through inhibition of neurotransmitters which ultimately result in downstream inhibition of inflammatory mediators, decreased fibroblast proliferation, and decreased expression of growth factors mediating fibrosis, resulting in a decrease in hypertrophic scarring. [22][23][24] A prospective clinical study of 19 patients undergoing monthly BTXA injections for 3 months showed significant improvement in patient-and physician-rated erythema, pruritus, and pliability scores.…”
Section: Injection Treatments For Hypertrophic Scar Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…21 One possible explanation for these results, is that due to delayed onset of muscle inactivity, BTXA injections must be performed 1 to 2 weeks prior to anticipated incision or laceration to have effect at the time of acute healing. 22 In addition to BTXA-induced wound immobility, in vitro studies and animal studies have also shown that BTXA may promote wound healing through inhibition of neurotransmitters which ultimately result in downstream inhibition of inflammatory mediators, decreased fibroblast proliferation, and decreased expression of growth factors mediating fibrosis, resulting in a decrease in hypertrophic scarring. [22][23][24] A prospective clinical study of 19 patients undergoing monthly BTXA injections for 3 months showed significant improvement in patient-and physician-rated erythema, pruritus, and pliability scores.…”
Section: Injection Treatments For Hypertrophic Scar Managementmentioning
confidence: 99%
“…22 In addition to BTXA-induced wound immobility, in vitro studies and animal studies have also shown that BTXA may promote wound healing through inhibition of neurotransmitters which ultimately result in downstream inhibition of inflammatory mediators, decreased fibroblast proliferation, and decreased expression of growth factors mediating fibrosis, resulting in a decrease in hypertrophic scarring. [22][23][24] A prospective clinical study of 19 patients undergoing monthly BTXA injections for 3 months showed significant improvement in patient-and physician-rated erythema, pruritus, and pliability scores. 25 Other injectable scar modulators such as 5-fluorouracil and bleomycin which have been used for nonsurgical treatment of keloid lesions and surgical excision or scar revision are beyond the scope of this article.…”
Section: Injection Treatments For Hypertrophic Scar Managementmentioning
confidence: 99%
“…2,5 5-Fluorouracil 5-Fluorouracil is a chemotherapeutic agent that has recently gained popularity in the treatment of hypertrophic scars and keloids. 4 This medication inhibits TGF-β2 in fibroblasts, preventing increased collagen production and deposition. 4 5-Flurouracil can be injected in the immediate postoperative phase in patients with a history of hypertrophic scars or keloids.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Raised scars, such as hypertrophic scars and keloids, are often first addressed with intralesional corticosteroids, primarily triamcinolone acetonide 3 . In addition to its anti‐inflammatory properties, corticosteroids minimize fibroblast and collagen synthesis and also decrease the production of ⍺1‐antitryptin and ⍺2‐macroglobulin, which are involved in keloid formation and are inhibitors of collagenase, 2,4 TGF‐β1, and TGF‐β2 5 . The initial dose for triamcinolone acetonide is usually between 5 and 20 mg/mL but can be increased up to 40 mg/mL depending on the severity of the scar being addressed 2,5 .…”
Section: Scar Revisionmentioning
confidence: 99%
See 1 more Smart Citation